Pengaruh Manajemen Pelayanan Muthawif terhadap Kepuasan Jamaah Umrah pada PT. Sinai Regional Bukittinggi - Zahara Rahmatullah; Gusrianti Gusrianti (ARZUSIN, 2026)
The management of muthawif services in the organization of Umrah pilgrimage has become a focus in several previous studies, but research that specifically discusses the direct effect of muthawif service management on Umrah pilgrims’ satisfaction remains limited, particularly in the context of local travel agencies. This study aims to analyze the effect of muthawif service management on Umrah pilgrims’ satisfaction at PT Sinai Regional Bukittinggi. This study employed a quantitative approach with an explanatory survey design. The research respondents were Umrah pilgrims selected through the purposive sampling technique. Data were collected using a Likert-scale questionnaire and were then analyzed using simple linear regression. The results show that muthawif service management has a significant effect on Umrah pilgrims’ satisfaction. Improving service quality, which includes the dimensions of reliability, responsiveness, assurance, empathy, and tangibles, contributes positively to the level of pilgrims’ satisfaction. These findings contribute to the development of studies on customer satisfaction and service quality in the context of religious services and broaden understanding of the important role of muthawif in creating an optimal worship experience. The conclusion of the study emphasizes that muthawif service management is an important factor in improving Umrah pilgrims’ satisfaction. The practical implication is that Umrah travel organizers need to continuously improve the competence and service quality of muthawif to strengthen service quality and pilgrims’ satisfaction.